Single versus double Perclose techniques for vascular closure during transfemoral transcatheter aortic valve replacement. Issue 7 (14th April 2022) - Hollowed, John; Akhondi, Andre; Rabbani, Amir; Oncel, Damla; Suh, William; Rafique, Asim; Kwon, Murray; Benharash, Peyman; Shemin, Richard; Aksoy, Olcay
Abstract: Introduction: The preferred approach for transcatheter aortic valve replacement (TAVR) is transfemoral. There has been widespread adoption of the Perclose Proglide TM device for vascular closure. Typically, two devices are deployed before upsizing the access sheath in the "preclose technique." Prior investigations have compared the use of a single device versus double device technique, but none have shown significant clinical benefit to either approach. Methods: Five hundred and six patients underwent transfemoral TAVR (TF‐TAVR) with single or double Perclose devices for vascular closure from July 2015 to February 2020. A retrospective review was conducted, and propensity‐matched analyses were used to account for differences in baseline characteristics. Results: In the matched analysis, there were 251 patients in the single Perclose group and 238 in the double. There was a statistically significant improvement in overall procedural success using the single closure device (94.6% vs. 88.5%, p = 0.009) This was defined as intraprocedural hemostatic control, lack of contrast extravasation, arterial dissection, occlusion, or stenosis >50% in the final crossover angiogram, as well as unimpaired limb perfusion without claudication throughout the index hospitalization. There was also a significant improvement in arterial dissection rates (0.6% vs. 4.6%, p = 0.004), stenosis >50% (1.3% vs. 4.4%, p = 0.028), and Valve Academic Research Consortium major vascular complications (1.8% vs. 4.9%, p = 0.038). Conclusion: A single Perclose device is a safe means of vascular closure during TF‐TAVR and may have important clinical benefits compared to the commonly used two‐device technique.